MA’HAD AL-ZAYTUN SEBAGAI RUANG TOLERANSI BERAGAMA DALAM BINGKAI PESANTREN MODERN - Tri Mustika Dewanti; Shoffan Abdussalam; Herry Suhardono; Ahlan Khoir Syah Rijal (STKIP Subang, 2026)
Indonesia is a country with a high level of pluralism, making religious tolerance a necessity in maintaining social stability. However, intolerance remains a serious challenge that requires concrete solutions, one of which is through educational institutions. This study aims to examine Ma'had Al-Zaytun as a space for religious tolerance within the framework of a modern Islamic boarding school, focusing on how Al-Zaytun realizes the values of tolerance through its educational approach and institutional activities. This study uses a qualitative approach with a library research method, where data sources were obtained from scientific journal articles selected based on the principles of recency and relevance. The results show that Ma'had Al-Zaytun consistently instills tolerance values through an integrative curriculum, the transformational leadership of Syaykh Panji Gumilang, teacher exemplary conduct, and various real activities involving cross-religious and cross-cultural communities. Al-Zaytun's tolerance practices are also proven to be in line with Law Number 5 of 2017, Article 29 Paragraph 2 of the 1945 Constitution, as well as the principles of Fiqh Siyasah and Islamic Law, making Al-Zaytun a reference model for inclusive and moderate Islamic educational institutions in Indonesia.